Burnout syndrome among healthcare professionals in the Fako division, Cameroon: Impact of physical activity and sleep quality - Elysée Claude Bika Lele; Jerson Mekoulou Ndongo; Ako Vera Ashu-akoh; Ahmadou; Jessica Guyot; Pierre Tchienrg Moueleu Ngalagou; Bienvenu Bongue; Nicholas Tendongfor; Clarisse Noel Ayina Ayina; Marie Yvonne Lobe Tanga; Samuel Honoré Mandengue; Peguy Brice Assomo Ndemba (AIMS Press, 2023)
Objectives: Burnout syndrome (BOS) is an affection mostly resulting from chronic job-related stress. Many studies have identified job-related and non-job-related factors associated with BOS. Our aim of this study was to assess the level of BOS in private and public hospital healthcare providers in Fako division, Cameroon and evaluate the impact of physical activity and sleep quality (SQ). Methods: The study was carried out in five randomly selected hospitals in Fako Division over a three-month period. Consenting doctors, nurses and laboratory technicians were recruited using consecutive sampling methods. Sociodemographic and professional characteristics were collected using a structured questionnaire. BOS was assessed using the Maslach Burnout Inventory Human Services Survey (MBI-HSS). Sleep quality (SQ) and physical activity (PA) were assessed using the Pittsburgh Sleep Quality Index (PSQI) and Global Physical Activity Questionnaire (GPAQ) respectively. Odd ratios and 95% confidence intervals were calculated and a statistical significance was set for p-value < 0.05. Results: The mean age was 32 ± 6 years and 70.9% female. BOS prevalence was 66.3% with 71.4% in females and 53.9% in males (p = 0.002). Of the 232 participants with BOS, 65.7%, 52% and 53.7% had moderate to high emotional exhaustion, depersonalization and decreased personal accomplishment, respectively. Moderate to high PA as well as poor SQ were not significantly associated with BOS while longer sleep duration (>8 h) was associated with a greater odd of BOS. Conclusions: The prevalence of BOS was high among healthcare professionals. While PA showed no protective effects, high sleep duration could increase its risk.